2020
DOI: 10.1103/physrevd.101.023001
|View full text |Cite
|
Sign up to set email alerts
|

White dwarfs as a probe of dark energy

Abstract: We investigate the radial density distribution of the dynamical dark energy inside the white dwarfs (WDs) and its possible impact on their intrinsic structure. The minimally-coupled dark energy with barotropic equation of state which has three free parameters (density, equation of state and effective sound speed) is used. We analyse how such dark energy affects the mass-radius relation for the WDs because of its contribution to the joint gravitational potential of the system. For this we use Chandrasekhar mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…Теоретичні дослідження темної матерії і темної енергії ведуться в Астрономічній обсерваторії Львівського національного університету імені Івана Франка. Учені Обсерваторії досліджують вплив динамічної темної енергії на рівновагу нейтронних зір [25,26], отримали обмеження на параметри темної енергії на основі космологічних даних про реліктове випромінювання, баріонні акустичні осциляції видимої матерії у Всесвіті та наднові зорі типу I a [27][28][29].…”
Section: з кафедри президії нан україниunclassified
“…Теоретичні дослідження темної матерії і темної енергії ведуться в Астрономічній обсерваторії Львівського національного університету імені Івана Франка. Учені Обсерваторії досліджують вплив динамічної темної енергії на рівновагу нейтронних зір [25,26], отримали обмеження на параметри темної енергії на основі космологічних даних про реліктове випромінювання, баріонні акустичні осциляції видимої матерії у Всесвіті та наднові зорі типу I a [27][28][29].…”
Section: з кафедри президії нан україниunclassified
“…Then we re-evaluated the distribution of dark energy and baryonic matter in the new potential. Such procedure was repeated until the solutions converged or the iteration limit exceeded (for more details see [7]). The solutions of the system of equations (3.4-3.5) for the dark energy component are shown in Fig.…”
Section: Distribution Of the Dark Energy Inside A Neutron Starmentioning
confidence: 99%
“…The local behavior of the perturbed dark energy has become an object of study in a series of works of the last decade. The impact of perturbation and clusterization of dark energy on the matter dynamics was studied on clusters of galaxies and galaxy scales (for example, in [1][2][3][4]) and on the astrophysical scale ( [5][6][7][8][9][10][11][12][13][14]). In general, studies have shown, that the local impact of minimally coupled perturbed dark energy is mostly negligible, except some specific value regions of its parameters space, which can be used for ruling out these values.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of dynamic dark energy with 2 ≪ 1 to change the shape and depth of the gravitational potential well of the compact stellar objects has been used in [40,41] to establish the lower limit for the effective sound speed of dark energy on the basis of the accuracies of the elements of the orbits of all bodies in the Solar system within the orbit of Saturn, as well as the Chandrasekhar mass-radius relation for white dwarfs. Both approaches indicate that the effective speed of sound of dark energy is greater than 10 −4 in the units of the speed of light.…”
Section: Dark Energy In the Vicinities Of Compact Astrophysical Objecmentioning
confidence: 99%